Sejarah Perkeretaapian Dan Relevansinya Terhadap Perekonomian Masyarakat Pulau Jawa 1917-2017 - M Kautsar Thariq Syah; Putri Lailatus Sa'adah; Riyan Haqi Khoerul Anwar (Dampeng: Journal of Art, Heritage and Culture, 2025)
This study aims to examine the strategic role of railways in Indonesia as a primary transportation infrastructure capable of addressing geographical challenges and supporting economic development. This study is important because railways function not only as a means of mobility but also as a driver of socio-economic growth across generations. The study uses a qualitative approach with a literature study method, based on historical literature sources, official archives, and relevant policy documents. Data are analyzed descriptively and analytically to trace the dynamics of railway development and its impact on people's lives. The research findings indicate that the construction of the first railway line in Java on June 17, 1864, by Governor General L.A.J. Baron Sloet van de Beele marked a milestone in transportation modernization in Asia. The existence of railways has been proven to increase mobilization efficiency, strengthen trade activities, accelerate regional integration, and remain relevant in the contemporary era, including supporting homecoming and tourism. The implications of this study emphasize the importance of railway revitalization as an environmentally friendly and sustainable transportation solution. The originality of the study lies in the emphasis on the historical and socio-economic dimensions that demonstrate the continuity of the role of railways from the colonial period to the modern era, thus providing academic and practical contributions to the study of sustainable transportation in Indonesia Abstrak: Penelitian ini bertujuan untuk mengkaji peran strategis perkeretaapian di Indonesia sebagai infrastruktur transportasi utama yang mampu menjawab tantangan geografis dan mendukung pembangunan ekonomi. Kajian ini penting karena kereta api tidak hanya berfungsi sebagai sarana mobilitas, tetapi juga sebagai penggerak pertumbuhan sosial-ekonomi lintas generasi. Penelitian menggunakan pendekatan kualitatif dengan metode studi pustaka, berdasarkan sumber literatur sejarah, arsip resmi, dan dokumen kebijakan yang relevan. Data dianalisis secara deskriptif-analitis untuk menelusuri dinamika perkembangan perkeretaapian serta dampaknya terhadap kehidupan masyarakat. Temuan penelitian menunjukkan bahwa pembangunan jalur kereta api pertama di Jawa pada 17 Juni 1864 oleh Gubernur Jenderal L.A.J. Baron Sloet van de Beele menjadi tonggak modernisasi transportasi di Asia. Keberadaan kereta api terbukti meningkatkan efisiensi mobilisasi, memperkuat aktivitas perdagangan, mempercepat integrasi wilayah, serta tetap relevan dalam era kontemporer, termasuk mendukung mudik dan pariwisata. Implikasi penelitian ini menekankan pentingnya revitalisasi perkeretaapian sebagai solusi transportasi ramah lingkungan dan berkelanjutan. Orisinalitas penelitian terletak pada penekanan dimensi historis dan sosial-ekonomi yang memperlihatkan kesinambungan peran kereta api dari masa kolonial hingga era modern, sehingga memberikan kontribusi akademik dan praktis bagi kajian transportasi berkelanjutan di Indonesia.